Occupancy, habitat, and abundance of the Sacramento Valley red fox. Issue 1 (16th August 2018) - Black, Kathleen M.; Preckler‐Quisquater, Sophie; Batter, Tom J.; Anderson, Stacy; Sacks, Benjamin N.
ABSTRACT: The Sacramento Valley red fox ( Vulpes vulpes patwin ) is a native subspecies of conservation need endemic to the northern portion of California's Central Valley, USA. We conducted an occupancy survey to investigate habitat use and obtain a crude, range‐wide estimate of abundance. We used 2 previously developed red fox distribution models based on presence‐only data to stratify sampling of 107 sites with baited cameras for ≥90 days during March 2013–June 2016, resulting in red fox detections at 30 sites. All detections occurred in 1 of the 93 sites where 1 or both previous presence‐only models predicted occurrence. Red fox occurrence was positively associated with dry agriculture, human development, and proximity to grassland, and negatively associated with wetlands and flooded agriculture. The models predicted that 34.21% of the 12, 000‐km 2 Sacramento Valley landscape contained red foxes, which we estimate corresponded to approximately 1, 600 breeding individuals. This estimate is comparable to that of the federally endangered California San Joaquin kit fox ( Vulpes macrotis mutica ), underscoring its potential vulnerability and conservation need. Targeted efforts to enhance its habitat, such as juxtaposition of grassland patches with agricultural and rural residential structures through conservation easements, could benefit conservation of the Sacramento Valley red fox. © 2018 The Wildlife Society. Abstract : Occupancy modeling indicated grassland, human development, and dry agricultural landcover as habitat variables most positively associated with Sacramento Valley red fox occurrence, predicting approximately 4, 000 km 2 of occupied habitat, or 1, 600 breeding adults. These findings illustrate the importance of prioritizing conservation of these habitat features in land‐use planning.